The post-colonial studies reader - Ashcroft, Bill, 1946-; Griffiths, Gareth, 1943-; Tiffin, Helen (Routledge, 1995)
"One of the most exciting features of English literatures today is the explosion of post-colonial literatures, those literatures written in English in formerly colonised societies. This field has given rise to a great range of theoretical ideas, concepts, problems and debates, and these have been addressed in a great range of articles, essays, talks and books published or written from every continent. This book brings together a selection of these theoretical issues in a way that indicates and celebrates the immense diversity of post-colonial theory. As such it will be an indispensable volume for students, teachers, researchers and theorists, and anybody interested in the field." "The uniqueness of this volume is in its range and comprehensiveness. By bringing together nearly ninety extracts from over fifty different writers, it demonstrates the vast spread of post-colonial theory, the degree to which such theory is emerging outside the metropolitan intellectual centres, and the significance such theory has in the practical political issues of living in this range of societies. This book makes accessible the full range of post-colonial theory, which otherwise would be either difficult or impossible for students, teachers or researchers to fully utilize."--Jacket.